2014
DOI: 10.1590/s0034-759020140510
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Legitimacy, Resource Access, and Organizational Outcomes

Abstract: Legitimidade cognitiva, acesso aos recursos e resultados organizacionais Legitimidad cognitiva, acceso a recursos, y resultados organizativos ABSTRACTPrevious research has demonstrated the importance of developing legitimacy initiatives in order to create new business opportunities, satisfy shareholders, and obtain access to resources. Within this framework, cognitive legitimacy plays a key role. Through a case study of six Spanish public universities, the authors measure the relationship between cognitive leg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 61 publications
(102 reference statements)
0
11
0
2
Order By: Relevance
“…It improves access to the indispensable resources it needs to survive and grow (Meyer & Rowan, 1977 ;Zucker, 1987 ). A number of studies have demonstrated this relationship (Baum & Oliver, 1992 ;Cruz-Suarez, Prado-Román, & Prado-Román, 2014 ;Díez-Martín, Prado-Román, & Blanco-González, 2013a ;Hannan & Carroll, 1992 ;Li, Yang, & Yue, 2007 ;Ruef & Scott, 1998 ). In the case of entrepreneurs, this is especially important because it allows them to overcome the liability of newness (Aldrich & Fiol, 1994 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It improves access to the indispensable resources it needs to survive and grow (Meyer & Rowan, 1977 ;Zucker, 1987 ). A number of studies have demonstrated this relationship (Baum & Oliver, 1992 ;Cruz-Suarez, Prado-Román, & Prado-Román, 2014 ;Díez-Martín, Prado-Román, & Blanco-González, 2013a ;Hannan & Carroll, 1992 ;Li, Yang, & Yue, 2007 ;Ruef & Scott, 1998 ). In the case of entrepreneurs, this is especially important because it allows them to overcome the liability of newness (Aldrich & Fiol, 1994 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In other words, society's welfare should be considered by every organization to ensure that their presence is acceptable (Farook, 2007). Consequently, the organization can easily access resources, market, and stakeholders' support to ensure its long-term survival and growth (Colleoni, 2013;Cruz-Suarez et al, 2014;Prado-Román et al, 2018) because the organization is viewed as legitimate in the eyes of stakeholders. On the other hand, the absence of legitimacy will lead the organization to fall into trouble.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ponterotto (2010) argues the phenomenon under study can be understood more clearly by listening to practitioners' opinions. Previous studies (e.g., Castelló & Lozano, 2011;Cruz-Suarez et al, 2014;Marais, 2012) mostly conducted in Western societies with different values and cultures from Indonesian Muslim society. Additionally, the discussion on this matter in the Indonesian Islamic banking context is not present yet.…”
Section: Introductionmentioning
confidence: 99%
“…States, just like organizations, must find competitive advantages (Porter, 2002) and adjust to the social and economic demands of its environment (Blanco-González, Díez-Martín, & Prado-Román, 2015, Díez-Martín et al, 2016) in order to survive and gain access to necessary resources. Institutions need to create an impression of sustainability and legitimacy so they will receive support from their stakeholders and be competitive (Cruz-Suárez, Prado-Román, & Prado-Román, 2014, Grigoli & Mills, 2014). Achieving this source of competitive advantage is the main reason states must pay attention to their legitimacy (Blanco-González et al, 2015; Díez-Martín, Blanco-González, & Prado-Román, 2016).…”
Section: Introductionmentioning
confidence: 99%